1999
DOI: 10.1161/01.str.30.4.749
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of Language-Related Brain Function During Recovery From Stroke

Abstract: Background and Purpose-This study was undertaken to correlate functional recovery from aphasia after acute stroke with the temporal evolution of the anatomic, physiological, and functional changes as measured by MRI. Methods-Blood oxygenation level-dependent contrast and echo-planar MRI were used to map language comprehension in 6 normal adults and in 2 adult patients during recovery from acute stroke presenting with aphasia. Perfusion, diffusion, sodium, and conventional anatomic MRI were used to follow physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
190
2
4

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 380 publications
(205 citation statements)
references
References 20 publications
8
190
2
4
Order By: Relevance
“…A number of right hemisphere regions showed increases in activity after remediation, including right inferior and superior frontal gyri, and middle temporal gyrus. These results are consistent with studies of recovery of function after left hemisphere damage that have shown increased activity in right hemisphere homologues of left hemisphere language areas associated with improved language ability (16)(17)(18).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A number of right hemisphere regions showed increases in activity after remediation, including right inferior and superior frontal gyri, and middle temporal gyrus. These results are consistent with studies of recovery of function after left hemisphere damage that have shown increased activity in right hemisphere homologues of left hemisphere language areas associated with improved language ability (16)(17)(18).…”
Section: Discussionsupporting
confidence: 91%
“…In addition to this ''normalizing'' effect of remediation, we hypothesized there would be changes in brain function in regions not normally active during phonological processing (compensatory effects), especially in right hemisphere homologues to left hemisphere language areas. Previous research on recovery of function after brain injury has shown that, in the face of left hemisphere damage, the right hemisphere can increase its activity in a compensatory manner (16)(17)(18). Because we suspected that the remediation may only partly ameliorate the left hemisphere disruptions, it was hypothesized that right hemisphere compenAbbreviations: fMRI, functional MRI; ROI, region of interest.…”
mentioning
confidence: 99%
“…Future fMRI studies of patients with brain damage may eventually reveal why a given patient has a particular type of comprehension deficit [cf. Thulborn et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…This may occur into ipsilateral cortex (Lazar et al, 1997;Rossini et al, 1998). When sufficient damage has occurred (Kertesz, Lau, & Polk, 1993), the contralateral hemisphere has also been shown to play a role in recovery from aphasia in adults (Thomas et al, 1997;Karbe et al, 1998;Thulborn et al, 1999). The hypothesis that arachnoid cysts lead to reorganization suggests that the location of language functions may be considerably different in this patient group than in a normal control group.…”
Section: Introductionmentioning
confidence: 92%